"No Standing Armies!" The Antiarmy Ideology in Seventeenth-Century England - Schwoerer, Lois G. (Johns Hopkins University Press, 2019)
Originally published in 1974. In her study of primary materials in England and the United States, Schwoerer traces the origin, development, and articulation in both Parliament and in the popular press of the attitude opposing standing armies in seventeenth-century England and the American colonies. Central to the criticism of armies at that time was the conviction that ultimate military power should be vested in Parliament, not the Crown. Schwoerer shows how the many diverse elements of England's antimilitarism, including political principle, propaganda, parliamentary tactics, parochialism, and partisanship, hardened with every confrontation between the Crown or Protector and Parliament. The author finds a general predisposition to distrust professional soldiers early in the century, and from the 1620s onward she notes opposition to a standing army in times of peace. Highlighting the growth of the antimilitary tradition, Schwoerer traces the development of this attitude from the Petition of Right in 1628 to the 1641-1642 crisis over the Militia Bill/Ordinance, the military settlements of 1660 and 1689, and the climactic events of 1667-1699. Schwoerer shows how the anti-standing-army ideology affected the constitutional thinking of the American colonists and manifested itself in the Constitution and the Bill of Rights. She addresses timeless questions of how to provide for a nation's defense while preserving individual liberty, citizen responsibility for military service, and the relationship of executive and legislative authority over the army.